X̄ charts with variable sample size - Costa, Antonio F B [UNESP] (My University, 1994)
The usual practice in using a control chart to monitor a process is to take samples of size n from the process every h hours. This article considers the properties of the X̄ chart when the size of each sample depends on what is observed in the preceding sample. The idea is that the sample should be large if the sample point of the preceding sample is close to but not actually outside the control limits and small if the sample point is close to the target. The properties of the variable sample size (VSS) X̄ chart are obtained using Markov chains. The VSS X̄ chart is substantially quicker than the traditional X̄ chart in detecting moderate shifts in the process.
Keywords: Graphic methods; Monitoring; Performance; Process engineering; Random processes; Sampling; Statistical methods; Control charts; Double sampling; Standard deviation; Statistical control; Variable sample size; Process control